The effect of thermal and non-thermal treatments on shelf-life of ready to drink whey-based functional beverages - Bhatia, R; Chauhan, K; Taneja, N; Kumar, V; Singh, G; Kaur, K (Plant Science Today, 2024)
Whey protein-based beverages are popular because of their many health benefits, high protein, pleasant flavor and vibrant hue. The hue of protein beverages is the most reliable barometer of how various quality characteristics will influence buyers' decisions. Protein beverages are typically processed using conventional thermal treatment, which diminishes their nutritional content and alters their appearance. Controlling the protein beverage quality and approximating the nutritional change can be achieved by examining microbial load during storage. This study analyzed the total microbial load such as coliform, yeast and molds of protein beverages, along with the impacts of various thermal (microwave, retort-pasteurization) and nonthermal (ultrasonication) treatments. The microbiological evaluation of the protein beverage was carried out at regular intervals (weekly) during the storage period under refrigeration and room temperature. In results, the protein beverage remained good in terms of overall acceptability and maintained the quality up to 90 days and 65 days after thermosonication treatment and was stored at refrigerated temperature (4 °C) followed by room temperature (28 °C) respectively. Hence, this study focuses on maximizing the shelf-life efficiency and maintaining protein beverage quality by using thermal and non-thermal procedures in tandem.